Scalable transfer of vertical graphene nanosheets for flexible supercapacitor applications. (13th September 2017) - Sahoo, Gopinath; Ghosh, Subrata; Polaki, S R; Mathews, Tom; Kamruddin, M
Abstract: Vertical graphene nanosheets (VGN) are the material of choice for application in next-generation electronic devices. The growing demand for VGN-based flexible devices for the electronics industry brings in restriction on VGN growth temperature. The difficulty associated with the direct growth of VGN on flexible substrates can be overcome by adopting an effective strategy of transferring the well-grown VGN onto arbitrary flexible substrates through a soft chemistry route. In the present study, we report an inexpensive and scalable technique for the polymer-free transfer of VGN onto arbitrary substrates without disrupting its morphology, structure, and properties. After transfer, the morphology, chemical structure, and electrical properties are analyzed by scanning electron microscopy, Raman spectroscopy, x-ray photoelectron spectroscopy, and four-probe resistive methods, respectively. The wetting properties are studied from the water contact angle measurements. The observed results indicate the retention of morphology, surface chemistry, structure, and electronic properties. Furthermore, the storage capacity of the transferred VGN-based binder-free and current collector-free flexible symmetric supercapacitor device is studied. A very low sheet resistance of 670 Ω/□ and excellent supercapacitance of 158 μ F cm −2 with 86% retention after 10 000 cycles show the prospect of the damage-free VGN transfer approach for the fabrication of flexible nanoelectronic devices.